NILAI-NILAI ISLAM SEBAGAI KUNCI DALAM PEMBENTUKAN KARAKTER PANCASILA TERHADAP PESERTA DIDIK DI SEKOLAH DASAR - Mubarok Somantri; Hany Handayani; Widodo Febriandi (STKIP Subang, 2023)
The lack of Pancasila character building in students is due to the factor of the lack of understanding of Islamic values that students need to know. The lack of Pancasila character building in students will result in the low formation of national character and the occurrence of social problems in students. Islamic values are a form of life principles taught by Islam. in its application, the values of Pancasila have a connection with Islamic values. Therefore Islamic values can help create the character of Pancasila in students. The method used in this paper is the literature study method. The data written is sourced from literature, such as articles and journals. The results of this paper are in the form of application in the formation of Pancasila character in students associated with Islamic values. From this paper it is concluded that the character of Pancasila can be formed through the cultivation of Islamic values, with the presence of Islamic values in students will be able to help students to become more Indonesian people who are oriented towards the character of Pancasila in students. With the formation of Pancasila character in students, it is hoped that it can build the character of the nation and avoid social problems.